The motifs and techniques of kelingkang old thread embroidery / Rose Dahlina Rusli - Rusli, Rose Dahlina (Institute of Graduate Studies, UiTM, 2018)
The art of kelingkan is a traditional form of Malay gold thread embroidery. Throughout history, the Malay culture has absorbed influences and adapted knowledge from other cultures while innovating and developing its own identity in arts and craft, including embroidery. Generally, kelingkan embroidery is known as gold work embroidery that uses flat gold metal strips and a special custom-made twoeyed needle; embroidered using the technique of tikam tembus are the main component required to complete the kelingkan process. Traditionally, the skill of embroidering kelingkan is passed down generations to generation. It was usually made for royalties and aristocrats due to its high cost and requirement for high maintenance. Recently, kelingkan embroidery seems to be acknowledged by Malay society. It is not only the preserve of royalty, but it can be worn by all. However, due to the lack of kelingkan embroiderers, this traditional embellishment art has become rare and cannot be commercialised. In addition, there is no proper documentation on its history, development, techniques and styles, as a reference for future generations. This research seeks to detail kelingkan embroidery in all aspects, including its origins, motifs, patterns, materials, tools and the techniques involves in its production. By doing so, the information about this dying craft could be spread out to the young generation and could be extend for a better future of it survival. The methodology used in this research is a qualitative descriptive research, conducted via field studies, interviews and visual observations. Through this research, it is hoped that a complete database can be established on the embroidery's originality and its future. The research also seeks to define and categorise different kelingkan techniques according to how they are stitched and their styles, in order to differentiate all the techniques involved. "Content analysis" will be use in analysing the data gathered throughout the investigation made. In addition, the research will suggest recommendations on improvements and conduct experimentation on reproducing the kelingkan needle and its embroidery styles, in order to generate new interest towards this traditional embroidery.